Svinfellinga saga : a new critical edition of BL Add. 11, 127 fol - Viljoen, Leonie (Department of English Language and Literature, 2016)
This is the first self-contained critical edition based on the most significant 17th century paper copy of the text of Reykjarfjarðarbók (AM 122b fol.), one of the two remaining vellum manuscripts of Sturlunga saga. Information about BL Add. 11,127 has hitherto been available only in annotations to editions of composite texts of the Sturlunga compilation and a few separate editions of its shorter sagas. This edition shows the nature of the 17th-century paper copy, its language, orthography and spelling, and reveals some linguistic change from the 14th century. Textual notes document all instances where BL Add. 11,127 differs from the other vellum manuscript, Króksfjarðarbók (AM 122a fol.), and two other paper copies: Stockholm pap. 8 4to and Adv. MS 21.3.17. The manuscripts have been examined and transcribed at first hand. The texts of the editions of Sturlunga saga by Vigfusson (1878), Kålund (1906-11), Jóhannesson et al. (1946) and Thorsson et al. (1988) are also considered. Lexical, syntactic, discursive and factual differences are shown to render a crisp, faster-moving, often more dramatic text, one which displays creativity and individuality in its processes of selection, abbreviation, addition and composition. The saga is placed in its social, historical and literary context and shown to reveal the tensions and contradictions of its age. The interpolation, hitherto excluded by editors, is shown to be part of the thematic and narrative design, linking the saga to the broader sweep of events in the Sturlung age which led to the loss of Iceland's independence. The glossary lists all words, their inflexions and conjugations, and gives grammatical and idiomatic explanations. The general notes, genealogical tables and the map of Iceland relevant to the text provide lexical, historical and literary background. Translations of sections difficult to trace elsewhere are appended.